AB0654 NAILFOLD MICROVASCULAR CHANGES IN MIXED CONNECTIVE TISSUE DISEASE: DIFFERENCES WITH SYSTEMIC SCLEROSIS. (June 2019) - Sulli, Alberto; Ferrari, Giorgia; Pizzorni, Carmen; Paolino, Sabrina; Smith, Vanessa; Alessandri, Elisa; Patanè, Massimo; Cutolo, Maurizio
Abstract : Background: Detailed nailfold capillary abnormalities have not been described in mixed connective tissue disease (MCTD) as well as their changes over time, unlike systemic sclerosis (SSc) which microvascular damage has been classified and validated by nailfold videocapillaroscopy (NVC) in specific and progressive scleroderma patterns ("Early", "Active", "Late") (1-5). Objectives: Aim of this study was to retrospectively compare detailed MCTD nailfold capillary abnormalities with those of SSc patients at first visit, and to monitor MCTD capillary changes over time. Methods: Ten patients (mean disease duration 6.4±4.2 years, mean age 50±19 years, ) affected by MCTD (Kasukawa's criteria) were enrolled. Patients with either anti-extractable nuclear antigen positivity different from U1RNP or anti-dsDNA antibodies were excluded. Main capillary parameters (scores of enlarged capillaries, giant capillaries, microhemorrhages, capillary ramifications, as well as absolute number of normal and total capillaries per linear millimetre) were assessed in MCTD patients at their first NVC analysis (T0), and during a three year follow-up. Furthermore, NVC parameters were compared at T0 with 10 random SSc patients matched for disease duration (6.4±4.2 years) and age (51±17 years). Statistical analysis was performed by non parametric tests. Results: The capillaroscopic scores of enlarged capillaries, giant capillaries and microhemorrhages were found significantly higher in SSc versus MCTD patients at T0 (2.50±0.5 vs 1.90±0.6 p=0.04, 1.63±0.7 vs 0.70±0.7 p<0.02, 1.25±0.7 vs 0.70±0.7 p=0.05, respectively). Moreover, the absolute number of both total capillaries and normal capillaries were found significantly lower in SSc versus MCTD patients (5.8±1.9 vs 7.6±1.6 p=0.04 and 0.45±1.0 vs 3.03±2.9 p= 0.009). On the contrary, no statistically significant difference was observed at T0 for the other capillary parameters (including capillary ramifications) between the two groups of patients. With the limit of a different pharmacological background among patients, no statistically significant variation of the scores, as well as of the absolute value of the above reported capillary parameters was observed during the 3 years of follow-up in MCTD patients. No statistically significant correlation was observed between capillary parameters and MCTD clinical aspects (Raynaud phenomenon, dysphagia, dyspnoea, sclerodactily, sicca syndrome, teleangectasias and artharlgia) at first visit and during follow-up. Conclusion: In a limited cohort of MCTD patients with an average disease duration of 6.4 years and a follow-up of three years, the nailfold microvascular damage does not seem to be significantly progressive. Patients with MCTD seem to show less enlarged/giant capillaries, and larger absolute number of total and normal capillaries than SSc patients. References: [1] De Holanda Mafaldo DA, et al. Lupus. 2007; 16:254–8. 2.. Cappelli S, et al. Semin arthritis Rheum. 2012; 41:589-98. [3] .Cutolo M. et al. Best Pract Res Clin Rheumatol 2008; 22:1093-108. [4] .Cutolo M. et al. J Rheumatol. 2000; 27:155-60. [5] Sulli a, et al. Arthritis Rheum. 2012;64:821-5. Disclosure of interests: None declared